Alleviating groundwater depletion while realizing food security for sustainable development. (20th March 2023) - Wei, Dan; Wang, Xinglong; Luo, Ning; Zhu, Yupeng; Wang, Pu; Meng, Qingfeng
Abstract: Groundwater depletion was one of humanity's greatest challenges for both food and environmental security. Here we tried to address these challenges through a meta-analysis in three major global groundwater-depleted agricultural regions and a case study with the long-term field experiment with factorable and systematic solutions. We showed groundwater depletion was particularly evident in the important regions for global food production, such as the High Plains of the United States, the Ganges Plains of India, and North China Plain, resulting from a 262.5 mm gap between crop water demand and rainfall. In order to solve this problem, the long-term field study in North China Plain indicated that the factor adjustment (minimum irrigation) within the traditional system and systematic change from traditional wheat-maize rotation to double-cropped maize could achieve both sustainable groundwater use and high calorie yield, accompanying by low integrated environmental impacts. Our results provided essential insights in similar areas for the United Nations Sustainable Development Goals for food and environmental security. Highlights: It was urgent to alleviate groundwater depletion together with food security. We firstly did a meta-analysis in three global groundwater-depleted regions. The field trial addressed the challenge with factorable and systematic solutions. Min.W/M and M-M could achieve sustainable groundwater use and high calorie yield.